Nanostructured Carbon-Nitrogen-Sulfur-Nickel Networks Derived From Polyaniline as Bifunctional Catalysts for Water Splitting - Djara, Razik; Holade, Yaovi; Merzouki, Abdelhafid; Lacour, Marie-Agnès; Masquelez, Nathalie; Flaud, Valerie; Cot, Didier; Rebiere, Bertrand; van der Lee, Arie; Cambedouzou, Julien; Huguet, Patrice; Tingry, Sophie; et al. (Frontiers in Chemistry, 2020)
The development of reliable production routes for sustainable hydrogen (H2), which is an essential feedstock for industrial processes and energy carrier for fuel cells. It appears to be an unavoidable alternative to significantly reduce the dependence on conventional energy sources based on fossil fuels without increasing the atmospheric CO2 levels. Among the different power-to-X scenarios to access high purity H2, the electrochemical approach based on the electrolysis parades as a promising sustainable solution at either the small or large industrial scales. However, the practical realization of this opportunity of paramount importance faces several challenges including the efficient design of cost-effective catalytic materials to be used as a cathode with improved intrinsic and durable activity. In this contribution, we report the design and development of efficient nanostructured catalysts for the electrocatalytic hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in aqueous media, whereby noble metal-free elements are embedded in a matrix of a conducting polymer, polyaniline (PANI). To increase the electrical conductivity and further the electrocatalytic ability towards HER of the chemically polymerized PANI in the presence of nickel (II) salt (nitrate, chloride), the as referred PANI-based materials have been firstly stabilized at mild temperature of 250-350 °C in air and secondly carbonized at 800-1000 °C under nitrogen gas to convert the chemical species into nitrogen, sulfur, nickel and carbon nanostructured networks (CNNs). Different physicochemical (TGA-DSC, Raman spectroscopy, XRD, SEM, EDX, ICP, CHNS, BET, and XPS) and electrochemical (voltammetry and electrochemical impedance spectrometry) methods have been integrated to characterize the as-synthesized CNNs materials and interrogate the relationship of material-to-performance. It has been found that those synthesis conditions allow increasing substantially the electrocatalytic performance towards HER and OER in alkaline media in terms of the onset potential, charge transfer resistance and overpotential at the specific activity of 10 milliamps per square centimeter, thus ranking the present materials among the most efficient noble metal-free catalysts and possible candidates for integration in practical low-energy consumption alkaline electrolyzers